2017
DOI: 10.1039/c7qo00400a
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-catalyzed direct asymmetric reductive amination of aromatic ketones

Abstract: Diphenylmethanamine offers excellent stereocontrol and easy deprotection to provide primary amines in the studied asymmetric reductive amination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the first step, esterification between compound 1 and 2 was carried out under mild conditions to afford 3 in quantitative yield, which is the key intermediate and substrate for next step. On the basis of our group’s early work [ 21 , 22 , 23 ], the catalytic system of iridium–monodentate phosphoramidite and a few additives were adopted. The monodentate phosphoramidite chiral ligands are based on BINOL back-bone, which is a cheap and readily available bulk chemical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first step, esterification between compound 1 and 2 was carried out under mild conditions to afford 3 in quantitative yield, which is the key intermediate and substrate for next step. On the basis of our group’s early work [ 21 , 22 , 23 ], the catalytic system of iridium–monodentate phosphoramidite and a few additives were adopted. The monodentate phosphoramidite chiral ligands are based on BINOL back-bone, which is a cheap and readily available bulk chemical.…”
Section: Resultsmentioning
confidence: 99%
“…Efficient and practical asymmetric synthesis of rivastigmine is still highly desired. Recently we have demonstrated that diphenylmethylamine is a universal amine source for the direct asymmetric reductive amination (DARA) of various ketones, catalyzed by iridium and readily available phosphoramidite ligand based on BINOL [ 21 , 22 , 23 ]. Here we report the convenient synthesis of ( S )-rivastigmine applying the DARA strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the intramolecular DARAs 16 23 , most reported N-sources of DARAs generally fall into three categories: inorganic ammonium salts 24 29 /ammonia 30 for the synthesis of primary amines; aryl amines 31 – 35 , the popularly applied N-sources, albeit often times the N -Ar group in the product is not desired and needs to be removed, which lead to secondary chiral amine products; and one example of secondary amine sources for the construction of tertiary chiral amine products 36 . Besides, there are some other sporadically reported special amines, including benzyl amines 37 , 38 , diphenylmethylamine 39 41 , hydrazine 42 , and hydrazides 43 , 44 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Previously there was only one example that utilized an alkyl amine, MeNH 2 , as the N -coupling partners in transition-metal-catalyzed DARAs 45 , and some instances in which special alkyl amines, such as benzyl amines 38 , 39 diphenylmethylamine 39 41 , and allylamine 46 , were used. Even the literature for the asymmetric hydrogenation of corresponding N -alkyl imines to directly form the N -alkyl amines are extraordinary scarce 47 52 , of which in two cases the N -alkyl amines were in situ transformed into N -SiH 2 Ph and N -Boc products in order to decrease the inhibitory effects on the catalysts 49 51 .…”
Section: Introductionmentioning
confidence: 99%
“…A few literature reports are available for the enantioselective synthesis of 1, in which the chiral center was developed by chiral poll approach [6,7,8], asymmetric hydrosilylation of imine [9,10,11], asymmetric reductive acylation of a ketoxime [12], diastereoselective addition of Grignard reagent [13], organolithium and dimethylzinc to imines bearing a chiral auxiliary [14,15,16], reductive amination of aromatic ketone [17,18,19], diastereoselective Nalkylation of amines with racemic alcohol [20,21], chiral ligand-promoted cobalt-catalysed radical hydroamination of alkene [22] or enantioselective arylation of aliphatic imines [23]. However, most of these methods have several drawbacks, such as tedious and time consuming experiments, unavailability or expensive chiral starting materials, low yield and lower enantiomeric purity, etc.…”
mentioning
confidence: 99%